Improving multiple aesthetics produces better graph drawings - Huang, Weidong; Eades, Peter; Hong, Seok-Hee; Lin, Chun-Cheng (Journal of visual languages and computing, 2013)
Many automatic graph drawing algorithms implement only one or two aesthetic criteria since most aesthetics conflict with each other. Empirical research has shown that although those algorithms are based on different aesthetics, drawings produced by them have comparable effectiveness. The comparable effectiveness raises a question about the necessity of choosing one algorithm against another for drawing graphs when human performance is a main concern. In this paper, we argue that effectiveness can be improved when algorithms are designed by making compromises between aesthetics, rather than trying to satisfy one or two of them to the fullest. We therefore introduce a new algorithm: BIGANGLE. This algorithm produces drawings with multiple aesthetics being improved at the same time, compared to a classical spring algorithm. A user study comparing these two algorithms indicates that BIGANGLE induces a significantly better task performance and a lower cognitive load, therefore resulting in better graph drawings in terms of human cognitive efficiency. Our study indicates that aesthetics should not be considered separately. Improving multiple aesthetics at the same time, even to small extents, will have a better chance to make resultant drawings more effective. Although this finding is based on a study of algorithms, it also applies in general graph visualization and evaluation. ► We have introduced cosine force, which is to increase the size of crossing angles. ► We have introduced sine force, which is to increase the angular resolution of vertices. ► We have introduced and implemented a force-directed algorithm, which improves multiple aesthetics at the same time. ► We have conducted a human study, which was the first to examine the collective effect of multiple aesthetics on humans. ► We have presented empirical evidence showing that improving multiple aesthetics produces better graph drawings.